Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.nanolett.6b04383
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Graphene and Its Derivatives for Liquid-Phase Transmission Electron Microscopy of Radiation-Sensitive Specimens

Abstract: One of the key challenges facing liquid-phase transmission electron microscopy (TEM) of biological specimens has been the damaging effects of electron beam irradiation. The strongly ionizing electron beam is known to induce radiolysis of surrounding water molecules, leading to the formation of reactive radical species. In this study, we employ DNA-assembled Au nanoparticle superlattices (DNA-AuNP superlattices) as a model system to demonstrate that graphene and its derivatives can be used to mitigate electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
181
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(185 citation statements)
references
References 60 publications
3
181
1
Order By: Relevance
“…GLCs have shown superior sample preservation under low to moderate electron dose conditions. Cho et al have studied gold‐conjugated DNA molecules in both GLC and silicon‐based liquid holder under the same electron beam conditions to compare undesired electron beam effects on proteins. Interestingly, observations showed that graphene sheets preserve the sample immaculately under electron doses as high as 250 e (Å 2 s) −1 , while the same experiment resulted in DNA destruction in silicon‐based liquid holder.…”
Section: Radiolysis and Beam Damage Mitigation In Glcsmentioning
confidence: 99%
See 1 more Smart Citation
“…GLCs have shown superior sample preservation under low to moderate electron dose conditions. Cho et al have studied gold‐conjugated DNA molecules in both GLC and silicon‐based liquid holder under the same electron beam conditions to compare undesired electron beam effects on proteins. Interestingly, observations showed that graphene sheets preserve the sample immaculately under electron doses as high as 250 e (Å 2 s) −1 , while the same experiment resulted in DNA destruction in silicon‐based liquid holder.…”
Section: Radiolysis and Beam Damage Mitigation In Glcsmentioning
confidence: 99%
“…In yet another study, it was reported that electron‐beam damage on dry MoS 2 crystals was reduced considerably once the sample was sandwiched between layers of graphene . Although the damage mitigation behavior of graphene has been attributed to its high electrical conductivity, the radical scavenging behavior of graphene and its derivatives, graphene oxide and graphene quantum dots, under in situ electron microscopy conditions has also been demonstrated . Loading electron scavenger agents in GLC, i.e., metallic ions, NaCl, glycerol, and n ‐propyl gallate, is another strategy to further mitigate radiolysis defects on susceptible specimens .…”
Section: Radiolysis and Beam Damage Mitigation In Glcsmentioning
confidence: 99%
“…This design was adopted in a study wherein a liquid flow holder system manufactured by Protochips Inc. was intended to deliver TEM imaging for gold nanoparticles in a thin layered saline water environment (Klein et al 2011). Further, improvisation of these liquid cells led to the use of graphene as a thinner window membrane material (Cho et al 2017). The advantage of using graphene cells was evident from a more desirable display of spatial resolution owing to minimal scattering of the bombarded electrons (Yuk et al 2012).…”
Section: Advancements In Liquid Em Technology and Instrumentationmentioning
confidence: 99%
“…Recently with improvised technological experimentations, liquid EM has penetrated in material-physical studies involving complex phenomena such as formation, growth, transformation, etching, nucleation and interactions of nanoparticles in solvated systems (Kim et al 2018;Lee et al 2017;Zhu et al 2018). Moreover, the use of Graphene in closedliquid cell has gained momentum owing to its powerful advantage as an optimum window material for atomic resolution TEM or STEM (Cho et al 2017;Yuk et al 2012;Textor and de Jonge 2018;Au-Chang et al 2019;Yuk et al 2014). This has led to a cascade of successive studies easing the way for an efficient liquid-handling protocol.…”
Section: Advantageous Potential Of Liquid Emmentioning
confidence: 99%
“…The electron pathway through both the SiN and water induces significant electron scattering . Graphene, on the other hand, is a single atomic layer that causes minimal background electron scattering . Moreover, graphene is a thermal and electrical conductor that prevents beam‐induced damage by facilitating fast energy dissipation .…”
Section: Introductionmentioning
confidence: 99%